Yeah, Binomial King is here.

Algebra Level 3

( 3 + x 2015 + x 2017 ) 2016 = a 0 + a 1 x + a 2 x 2 + . . . + a n x n \left( 3 + { x }^{ 2015 } + { x }^{ 2017 } \right)^{ 2016 } = { a }_{ 0 } + { a }_{ 1 }x + { a }_{ 2 }{ x }^{ 2 } + ... + { a }_{ n }{ x }^{ n }

Given the above, find the value of

a 0 1 2 a 1 1 2 a 2 + a 3 1 2 a 4 1 2 a 5 + a 6 + . . . { a }_{ 0 } - \frac { 1 }{ 2 } { a }_{ 1 } - \frac { 1 }{ 2 } { a }_{ 2 } + { a }_{ 3 } - \frac { 1 }{ 2 } { a }_{ 4 } - \frac { 1 }{ 2 } { a }_{ 5 } + { a }_{ 6 }+...

1 0 2 2016 { 2 }^{ 2016 } 3 2016 { 3 }^{ 2016 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Aug 10, 2017

Let f ( z ) = ( 3 + z 2015 + z 2016 ) 2016 f(z) = \left(3+z^{2015}+z^{2016}\right)^{2016} , then:

f ( x ) = a 0 1 2 a 1 1 2 a 2 + a 3 1 2 a 4 1 2 a 5 + a 6 f ( z ) = a 0 ( 1 2 i 3 2 ) a 1 ( 1 2 + i 3 2 ) a 2 + a 3 ( 1 2 i 3 2 ) a 4 ( 1 2 + i 3 2 ) a 5 + a 6 = a 0 + a 1 e i 2 π 3 + a 2 e i 4 π 3 + a 3 e i 6 π 3 + a 4 e i 8 π 3 + a 5 e i 10 π 3 + a 6 e i 12 π 3 + = a 0 + a 1 ω + a 2 ω 2 + a 3 ω 3 + a 4 ω 4 + a 5 ω 5 + a 6 ω 6 + \begin{aligned} f({\color{#3D99F6}x}) & = a_0 - \frac 12 a_1 - \frac 12 a_2 + a_3 - \frac 12 a_4 - \frac 12 a_5 + a_6 - \cdots \\ f({\color{#D61F06}z}) & = a_0 - \left(\frac 12 - i\frac {\sqrt 3}2\right) a_1 - \left(\frac 12 + i\frac {\sqrt 3}2\right) a_2 + a_3 - \left(\frac 12 - i\frac {\sqrt 3}2\right) a_4 - \left(\frac 12 + i\frac {\sqrt 3}2\right) a_5 + a_6 - \cdots \\ & = a_0 + a_1 e^{i\frac {2\pi}3} + a_2 e^{i\frac {4\pi}3} + a_3 e^{i\frac {6\pi}3} + a_4 e^{i\frac {8\pi}3} + a_5 e^{i\frac {10\pi}3} + a_6 e^{i\frac {12\pi}3} + \cdots \\ & = a_0 + a_1 \omega + a_2 \omega^2 + a_3 \omega^3 + a_4 \omega^4 + a_5 \omega^5 + a_6 \omega^6 + \cdots \end{aligned}

z = ω where ω is the third root of unity. f ( x ) = ( f ( ω ) ) ( z ) is the real part of z . = [ ( 3 + ω 2015 + ω 2016 ) 2016 ] Note that ω 3 = 1. = [ ( 3 + ω 2 + ω ) 2016 ] Note that ω 2 + ω + 1 = 0. = [ ( 3 1 ) 2016 ] = 2 2016 \begin{aligned} \implies z & = \omega & \small \color{#3D99F6} \text{where }\omega \text{ is the third root of unity.} \\ f(x) & = \color{#3D99F6}\Re \left(f(\omega) \right) & \small \color{#3D99F6} \Re(z) \text{ is the real part of }z. \\ & = \Re \left[\left(3+\omega^{2015}+\omega^{2016}\right)^{2016}\right] & \small \color{#3D99F6} \text{Note that }\omega^3 = 1. \\ & = \Re \left[ \left(3+\omega^2+\omega \right)^{2016}\right] & \small \color{#3D99F6} \text{Note that }\omega^2 + \omega + 1 = 0. \\ & = \Re \left[ \left(3-1 \right)^{2016}\right] \\ & = \boxed{2^{2016}} \end{aligned}

@Chew-Seong Cheong , thanks for the more elaborated solution.

Priyanshu Mishra - 3 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...